2010
DOI: 10.1063/1.3477191
|View full text |Cite
|
Sign up to set email alerts
|

Proposed truncated Cu–Hf tight-binding potential to study the crystal-to-amorphous phase transition

Abstract: Articles you may be interested inInteratomic potential to predict the favored and optimized compositions for ternary Cu-Zr-Hf metallic glasses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is one of the few binary metallic alloys capable of glass formation in the bulk 29 . The glass forming region is expected to be between ~30–70 at.% hafnium for samples prepared via melting spinning (cooling rate ~10 3 –10 7 K/s) 30 . Here STM observations on Cu 100− x Hf x are presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the few binary metallic alloys capable of glass formation in the bulk 29 . The glass forming region is expected to be between ~30–70 at.% hafnium for samples prepared via melting spinning (cooling rate ~10 3 –10 7 K/s) 30 . Here STM observations on Cu 100− x Hf x are presented.…”
Section: Resultsmentioning
confidence: 99%
“…29 The glass forming region is expected to be between ∼ 30 − 70 at.% hafnium for samples prepared via melting spinning (cooling rate ∼ 10 3 -10 7 K/s). 30 Here STM observations on Cu 100−x Hf x are presented. The surface is found to have hillock features with sizes dependent on Hf concentration, and pervasive dynamics manifested as hopping clusters.…”
Section: Resultsmentioning
confidence: 99%
“…3,4,[18][19][20] For instance, Qin et al 3 have reported that the Cu-Hf-Ti-Nb glassy alloys synthesized via rapid solidification could show a high glass-forming ability and high corrosion resistance, as well as improved mechanical properties. Jia et al 4 have synthesized glassy alloy rods with diameters of up to 10 mm in the Cu-Hf-Al system, and the alloys feature high strength and decent ductility.…”
Section: Introductionmentioning
confidence: 99%